Highway 59 : Bluebird, Bluebird - Book 1 - Locke, Attica (New York : Mulholland Books, an imprint of Little, Brown and Company, 2018)
When it comes to law and order, East Texas plays by its own rules--a fact that Darren Mathews, a black Texas Ranger, knows all too well. Deeply ambivalent about growing up black in the lone star state, he was the first in his family to get as far away from Texas as he could. Until duty called him home. When his allegiance to his roots puts his job in jeopardy, he travels up Highway 59 to the small town of Lark, where two murders--a black lawyer from Chicago and a local white woman--have stirred up a hornets nest of resentment. Darren must solve the crimes--and save himself in the process--before Larks long-simmering racial fault lines erupt. A rural noir suffused with the unique music, color, and nuance of East Texas, Bluebird, Bluebird is an exhilarating, timely novel about the collision of race and justice in America."--
Keywords: Texas Rangers; Fiction; African American police -- Fiction; Murder -- Investigation; Fiction; Race relations -- Fiction; Detective and mystery stories, American; Texas, East; Fiction; Thrillers (Fiction); Noir fiction; Noir fiction; Thrillers (Fiction)